Innovation capabilities and financing constraints of family firms - Dorothea Schäfer; Andreas Stephan; Jennifer Solórzano Mosquera (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Using the 2007 Mannheim innovation survey, we investigate whether family firms are more financially constrained than other firms and how this affects both innovation input as well as innovation outcomes such as market and firm novelties or process innovations. Based on the CDM framework, estimation of the recursive system of equations shows that family businesses are more likely to be constrained and have, on average, lower innovation input. Surprisingly, however, this doesnot reduce their innovation outcomes as, on average, family firms have the same level of innovation outcomes as nonfamily firms.
Keywords: D32; G32; O32; 330; Innovation; Capability; Financing Constraints; Family Firms; CDM